The Use of Endovascular Laser Coagulation in the Recurrence of Varicose Veins of the Lower Extremities - Ergashev Ulugbek Yusufjanovich; Minavarkhojayev Ravshankhuja Rakhmatkhuja ogli; Zokhirov Adkhamjon Rafiqovich; Malikov Nodir Muzaffar ugli; Mukhamedova Shahnoza Yusufjon qizi (Scientific Trends, 2023)
The purpose of the study: to study the effectiveness of endovascular laser coagulation in patients with recurrent varicose veins of the lower extremities.
Keywords: recurrence of varicose veins of the lower extremities, endovasal laser coagulation, ultrasonic angioscanning , quality of life.